问题
解答题
先化简,再求值: (1)(
(2)(
(3)(
(4)(1-
(5)
(6)(
(7)(
(8)
|
答案
(1)原式=
•2(a-1)-(a+1) (a+1)(a-1)
=(a+1)(a-1) a
,a-3 a
当a=2时,原式=
=-2-3 2
;1 2
(2)原式=
•a+2-2(1-a) (1+a)(1-a)
=1-a a
,3 1+a
当a=
-1时,原式=3
=3 1+
-13
;3
(3)原式=
•(x-2)2 x
=x-2,x(x+2) (x+2)(x-2)
当x=-1时,原式=-1-2=-3;
(4)原式=
•x+3-1 x+3
=x(x+3) (x+2)(x-2)
,x x-2
当x=6时,原式=
=6 6-2
;3 2
(5)原式=
•x-2 (x+1)(x-1)
+(x+1)2 2(x+1)
=1 x-1
=x-2+2 x-1
,x x-1
当x=
+1时,原式=2
=
+12
+1-12
;2+ 2 2
(6)原式=
•(x+2)(x-2) x-2
=1 x(x+2)
,1 x
当x=
时,原式=2
;2 2
(7)原式=
•a+b+a-b (a+b)(a-b)
=a+b ab
,2 b(a-b)
当a=
+1,b=2
时,原式=2
=2
(2
+1-2
)2
;2
(8)原式=
•(x+2)2 x+2
=1 x(x+2)
,1 x
当x=
时,原式=2
.2 2